Counseling research quantitative, qualitative, and mixed methods - Sheperis, Carl; Young, J. Scott; Daniels, M. Harry (Boston, MA Pearson Learning Solutions, a Pearson Education Company, 2017)
The text introduces reader to the basics of how to do research-from formulating a problem, doing a literature review, selecting a design, collecting and analyzing data, through reporting results. It also provides readers with the information they need to become intelligent consumers of published research. Covering a broad range of quantitative, qualitative, and mixed methods designs, as well as action research and program evaluation, the text presents the most common types of research used in the field of counseling.
Contemporary issues in counseling research / Carl J. Sheperis -- Ethical consideration in the practice of research / Kelly L. Wester and Erik Hines -- Reviewing the literature / Donna S. Sheperis and Michelle Perepiczka -- Methodological issues / Julia L. Whisenhunt and Mary Alice Varga -- Basic statistical concepts and descriptive statistics / Laura K. Jones -- Experimental designs / A. Stephen Lenz -- Predictive designs / Carl J. Sheperis, Joshua C. Watson and Laura Haddock -- Single-case research designs / Edina L. Renfro-Michel and A. Stephen Lenz -- Case study research / Cheryl Pence Wolf, M. Harry Daniels, and Eric S. Thompson -- Grounded theory methodology / Matthew R. Buckley -- Phenomenological designs: the philosophy of phenomenological research / J. Scott Young -- Narrative research: interpreting lived experience / Kylie Dotson Blake -- An overview of survey research / J. Scott Young -- Mixed method designs / Carl J. Sheperis and April Heiselt -- Action research / Eric S. Thompson, Cheryl Pence Wolf, and M. Harry Daniels -- Program evaluation / M. Harry Daniels, Eric S. Thompson, and Cheryl Pence Wolf -- Data management and data analysis software / Rebecca K. Frels -- Developing a research report / Craig S. Cashwell and Kerrie K. Fuenfhausen.
Taken from: Counseling research : quantitative, qualitative, and mixed methods, second edition by Carl J. Sheperis, J. Scott Young, M. Harry Daniels.
Includes bibliographical references (pages 385-401) and index.
Keywords: Counseling -- Research